A single case study on the effectiveness of aromatherapy and counseling in adolescents with ayurvedic Vata constitution - Moon, Sun Hee; Cheong, Mee Sook (Edelweiss Applied Science and Technology, 2025)
This single-case qualitative study investigated the therapeutic effects of aromatherapy and counseling on a 14-year-old female adolescent with a Vata constitution, as defined by Ayurvedic principles. Following approval from the Institutional Review Board (IRB No. 8223-202403-HR-004-01), the intervention was conducted from January 1 to May 30, 2024, in H City. The participant (165 cm, 46 kg) experienced irregular menstruation, menstrual pain, academic stress, poor blood circulation, and irritable bowel syndrome. Twelve sessions took place over eight weeks, with each session comprising 25 minutes of counseling and 20 minutes of aromatherapy. Qualitative data were gathered through session summaries and analyses of the participant’s behavioral changes. The results showed significant improvements in both physical and psychological symptoms: menstrual irregularities and pain subsided, blood circulation and gastrointestinal comfort improved, and academic stress was notably reduced. The participant also demonstrated enhanced social engagement and a more positive outlook. Notably, Neroli and Lavender essential oils contributed to reducing anxiety and tension, and the continued use of aromatherapy yielded sustained benefits in daily life. These findings suggest that an integrative approach combining aromatherapy and counseling can be an effective complementary strategy for addressing stress and health-related issues in adolescents with a Vata constitution.